Fetal-Derived MyD88 Signaling Contributes to Poor Pregnancy Outcomes During Gestational Malaria - Barboza, Renato; Hasenkamp, Lutero; Barateiro, André; Murillo, Oscar; Peixoto, Erika Paula Machado; Lima, Flávia Afonso; Reis, Aramys Silva; Gonçalves, Lígia Antunes; Epiphanio, Sabrina; Marinho, Claudio R. F. (Frontiers in Microbiology, 2019)
Placental malaria (PM) remains a severe public health problem in areas of high malaria transmission. Despite the efforts to prevent infection poor outcomes in Plasmodium endemic areas, there is still a considerable number of preterm births and newborns with low birth weight resulting from PM. Although local inflammation triggered in response to malaria is considered crucial in inducing placental damage, little is known about the differential influence of maternal and fetal immune responses to the disease progression. Therefore, using a PM mouse model, we sought to determine the contribution of maternal and fetal innate immune responses to PM development. For this, we conducted a series of cross-breeding experiments between mice that had differential expression of the MyD88 adaptor protein to obtain mother and correspondent fetuses with distinct genetic backgrounds. By evaluating fetal weight and placental vascular spaces, we have shown that the expression of MyD88 in fetal tissue has a significant impact on PM outcomes. Our results highlighted the existence of a distinct contribution of maternal and fetal immune responses to PM onset. Thus, contributing to the understanding of how inflammatory processes lead to the dysregulation of placental homeostasis ultimately impairing fetal development.